Plan de negocios, mediante la aplicación de la metodología de Canvas /, para proponer la implementación del agroturismo en la hacienda Guingla, Parroquia Santa Cecilia, Cantón Lago Agrio - Caiza Vistín, Wilmer Arquímides (2018)
The Agrotourism in Ecuador is a new foreign exchange activity to improve local economies especially rural communities from a sustainable approach, you can see that the natural predominates, having an infinite diversity in fauna and flora. The Santa Cecilia parish belonging to the canton Lago Agrio of the province of Sucumbíos, is a parish surrounded by abundant flora and fauna, as well as agricultural and livestock production, which constitutes a very important source of income for the families of the parish and from the Lago Agrio canton. The problem in the canton Lago Agrio is not to have a diversification in alternative tourism products such as Agrotourism which has not allowed the tourist development in the canton and the province of Sucumbíos. Agrotourism as such is not a product that has been worked independently in the canton of Lago Agrio, and the peasant producers have not managed to constitute a sustainable agriculture, towards a potential tourist rural product. The General Objective of the present project was to design the business plan through the application of the CANVAS methodology, to propose the implementation of agrotourism in the "Hacienda Guingla", Santa Cecilia parish, Lago Agrio canton. The investigation was developed, the Guingla farm, of the Santa Cecilia parish, where 382 surveys and 4 interviews were applied to the owners and employees of the farm, the data obtained through the research instruments, allowed to determine the following results: On the results obtained, the proposal proposes a diagnosis within the Hacienda Guingla to determine the current status of its resources, as well as the identification of agricultural production, livestock, type of tourism, quality of service and infrastructure; concluding that the area has a great tourist potential in terms of natural resources, agricultural, livestock, the same that are developed in a sustainable way and thereby help to improve the quality of life of the inhabitants. Subsequently, based on the Business Plan using the CANVAS methodology, implement agro-tourism activities at the Guingla Farm, supported by strategic analysis and the theory of project preparation and evaluation. The conclusions refer to the objectives to be investigated in order to discuss fundamental parameters such as the agrotourism diagnosis of the canton and the Treasury.